Poverty status and the impact of social networks on smallholder technology adoption in rural Ethiopia - Liverpool-Tasie, Lenis Saweda; Winter-Nelson, Alex (International Food Policy Research Institute, 2010)
Despite the promise of many new farm technologies, technology adoption rates in Ethiopia remain low. This paper studies the impact of social networks on technology adoption through social learning. In addition to geographic networks, intentional relationships are considered. The differential impacts by network type, technology, and asset poverty status are explored. We find evidence that although social learning occurs, it is more consistent for households not in poverty traps than for those that are persistently asset poor. Social learning among rural households is stronger for more complex technologies and is associated with intentional relationships rather than with geographic networks.